Niacin restriction upregulates NADPH oxidase and ROS in human keratinocytes - Benavente, Claudia A. (2007)
NAD(+) is a substrate for many enzymes, including poly(ADP-ribose) polymerases and sirtuins, which are involved in fundamental cellular processes including DNA repair, stress responses, signaling, transcription, apoptosis, metabolism, differentiation, chromatin structure, and life span. Because these molecular processes are important early in cancer development, we developed a model to identify critical NAD-dependent pathways potentially important in early skin carcinogenesis. Removal of niacin from the cell culture medium allowed control of intracellular NAD. Unlike many non-immortalized human cells, HaCaT keratinocytes, which are immortalized and have a mutant p53 and aberrant NF-kB activity, become severely NAD depleted but divide indefinitely under these conditions. Niacin deficient HaCaTs develop a decreased growth rate due to an increase in apoptotic cells and an arrest in the G(2)/M phase of the cell cycle. Long- term survival mechanisms in niacin deficient HaCats involve accumulation of reactive oxygen species and increased DNA damage. These alterations result, at least in part, from increased expression and activity of NADPH oxidase, whose downstream effects can be reversed by nicotinamide or NADPH oxidase inhibitors. Our data support the hypothesis that glutamine is a likely alternative energy source during niacin deficiency and we suggest a model for NADPH generation important in ROS production.